Forest destructuring as revealed by the temporal dynamics of fundamental species - Case study of Santa Genebra Forest in Brazil - Farah, F. T.; Rodrigues, R. R.; Santos, F. A. M.; Tamashiro, J. Y.; Shepherd, G. J.; Siqueira, T. [UNESP]; Batista, J. L. F.; Manly, B. J. F. (Elsevier B.V., 2014)
Variation in the composition of the tree population is common throughout the history of a well-preserved forest community, with this natural process maintaining the forest structure and giving rise to ecological processes necessary for the perpetuation of the ecosystem. However, fragmentation of forests can lead to the collapse of such a structure, especially when natural thinning of the dominant tree species is accompanied by other significant changes. This paper traces changes in the composition of the community of a forest of relevant ecological interest in Campinas (SP, Brazil) as that forest moves toward deterioration as indicated by a massive loss of individuals of fundamental species composing the canopy and subcanopy. The death of trees of the species traditionally forming the canopy, the result of natural processes, was probably intensified by anthropic factors, and led to a general destructuring of the community. The aim of this paper is to demonstrate that the dynamics of these fundamental species can be used as an indicator of the conservation of the ecosystem, as well as indicating the installation of a process which will lead to the collapse of the structure if adequate measures of adaptive management are not taken before the destructuring is irreversible. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Secondary forest; Atlantic forest; Seasonal semideciduous forest; Fundamental species; Regime shift; Aspidosperma polyneuron